THE IMPLEMENTATION OF THE MARRIAGE AGE LIMIT - Dita Nabila Jania Liswan; Syamsul Bahri (JILPR Journal Indonesia Law and Policy Review, 2024)
Article 7, Paragraph (1) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage states that "Marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years." However, in practice, there are several cases of underage marriage without marriage dispensation in Kutapanjang District. The purpose of this study is to explain the implementation of Article 7, Paragraph (1) of Law Number 16 of 2019 concerning the Marriage Age Limit in Kutapanjang District, Gayo Lues Regency, and to identify the causes of underage marriage without a marriage dispensation. This research is empirical juridical research. The data were obtained through field research, primarily using interviews. The findings indicate that the implementation of Article 7, Paragraph (1) of Law Number 16 of 2019 concerning the Marriage Age Limit in Kutapanjang District, Gayo Lues Regency has not been fully effective, as several couples still do not comply with the regulations. As a result, the implementation of Article 7, Paragraph (1) in Kutapanjang District, Gayo Lues Regency has not been maximized. The factors contributing to underage marriages without marriage dispensation can be categorized into three: First, coercive circumstances where the female party is already pregnant, leading to an immediate marriage to avoid social disgrace for the family and community. Second, economic pressure, where families believe marrying off their children reduces the financial burden of supporting them. Third, rejection of a marriage dispensation request by the Sharia Court, leading to unofficial or unregistered marriages. It is recommended that the government, especially the Office of Religious Affairs (KUA), be more proactive in raising awareness about Law Number 16 of 2019, which amends Law Number 1 of 1974 regarding the Marriage Age Limit, to all levels of society.